2019
DOI: 10.31925/farmacia.2019.6.23
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Pattern of Antiepileptic Drugs in Southern Pakistan: A Retrospective Cohort Study in Tertiary Care Centres

Abstract: Epilepsy is the most occurring neurological disorder after stroke. Prevalence of epilepsy is about 9.99 per 1000 population in Pakistan. In recent years, about 14 new antiepileptic drugs (AEDs) have been marketed. Irrational drugs prescribing might decrease patient adherence with therapy and cause therapeutic failure. The aim of the current study was to evaluate the incidence of different types of epilepsy with syndromes and use of AEDs in patients with epilepsy in detail in a population, characterized by gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Data were collected from patients with epilepsy who received AEDs for the first time. Patients who received following top five prescribed anti-epileptic drugs as descending order are as follows, levetiracetam, valproic acid, carbamazepine, lamotrigine, lacosamide while phenobarbital, phenytoin, gabapentin, pregabalin and oxcarbazepine were considered as others AEDs [ 13 ]. Data of participants who died or left from the study due to any reason were not included.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were collected from patients with epilepsy who received AEDs for the first time. Patients who received following top five prescribed anti-epileptic drugs as descending order are as follows, levetiracetam, valproic acid, carbamazepine, lamotrigine, lacosamide while phenobarbital, phenytoin, gabapentin, pregabalin and oxcarbazepine were considered as others AEDs [ 13 ]. Data of participants who died or left from the study due to any reason were not included.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, pharmacoeconomics, adherence and persistence with AEDs have been reported using various methods in different countries [ 15 19 ]. In our previous study, we have reported the prescribing patterns of AEDs in Southern Pakistan [ 13 ]. However, according to our literature study, in Pakistan, no such study was conducted regarding the patient’s adherence and cost analysis of AEDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioavailability is reported to be approximately 90% for all oral formulations with enteric-coated forms possibly reaching 100% [30]. The anticonvulsant mechanism of action of valproic acid seems to be the cerebral increase of GABA, especially within the grey matter of the brain, which is involved in controlling and propagating convulsions [3,13]. The mechanism of action of valproic acid is still unclear, but it is assumed that while cerebral concentrations of gamma aminobutiric acid (GABA) increase, a decrease of monophosphate cyclic guanosine monophosphate is recorded (CGMP) [24].…”
Section: Introductionmentioning
confidence: 99%